2006
DOI: 10.1111/j.1439-0531.2005.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Field Fertility with Two Different Insemination Doses and the Effect of Sperm Morphology

Abstract: In swine artificial insemination, several dose regimens are applied, ranging from 1.5 x 10(9) to 6.0 x 10(9) spermatozoa per intra-cervical insemination dose. A lower sperm dose is more profitable for artificial insemination centres and offers a more effective use of superior boars. To evaluate fertility, 50 boars were used for a total of 10 773 homospermic first inseminations at a dose of 2 billion spermatozoa. In addition, 96 boars were used at a dose of 3 billion spermatozoa for 34 789 homospermic first ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 11 publications
3
36
0
1
Order By: Relevance
“…The average litter size produced when using frozen-thawed spermatozoa is below what most of the industry will accept (Ruiz-S anchez et al, 2006). Traditional analyses of boar spermatozoa that include motility, morphology and viability, are only moderately useful for identifying boars of low fertility (Flowers, 1997;Gadea et al, 2004;Gadea, 2005;Alm et al, 2006;Lovercamp et al, 2007;Broekhuijse et al, 2012). Knowledge of the causes of reduced fertility due to cryopreservation is incomplete, although there are reductions in routinely measured sperm traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average litter size produced when using frozen-thawed spermatozoa is below what most of the industry will accept (Ruiz-S anchez et al, 2006). Traditional analyses of boar spermatozoa that include motility, morphology and viability, are only moderately useful for identifying boars of low fertility (Flowers, 1997;Gadea et al, 2004;Gadea, 2005;Alm et al, 2006;Lovercamp et al, 2007;Broekhuijse et al, 2012). Knowledge of the causes of reduced fertility due to cryopreservation is incomplete, although there are reductions in routinely measured sperm traits.…”
Section: Introductionmentioning
confidence: 99%
“…There are likely additional types of cellular damage due to cryopreservation that are not detected in standard semen analysis, given the low correlation between fertility and traditional microscopic evaluation. Numerous attempts have been made to identify in vitro sperm parameters that that are directly related to fertility (Holt et al, 1997;Tardif et al, 1999;Larsson & Rodrıǵuez-Martıńez, 2000;Waberski et al, 2005;Alm et al, 2006;Broekhuijse et al, 2012;Schulze et al, 2013). However, novel assays that measure sperm interactions within the female reproductive tract and with oocytes may be more predictive of in vivo function as well as useful when identifying reasons for reduced fertility (Fazeli et al, 1997;Braundmeier et al, 2004;Collins et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, negative correlations (P >0.05) were observed between conception rate and major sperm defects as well as minor morphological ones. Conversely, boar sperm morphology has been reported to have limited positive predictive value for field fertility (Alm et al, 2006). Although negative correlations were found between fertility and morphological defects, Waberski et al (1990) reported that sperm morphology may assist with boar selection for AI as it provided information about spermatogenesis.…”
Section: Dead Sperm Live Spermmentioning
confidence: 99%
“…Sperm morphology assessment consists of determining the percentage of spermatozoa with defective morphological structure and the share of spermatozoa with major or minor defects (25). Male fertility has been shown to depend on the incidence of morphologically defective spermatozoa (1). Even a slight increase in the percentage of spermatozoa with major defects can lower male fertility (7).…”
Section: Introductionmentioning
confidence: 99%